2015
DOI: 10.12968/denu.2015.42.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic rehabilitation of the gagging patient using acrylic training plates

Abstract: Patients with a hyper-responsive gag reflex pose dentists with a challenging problem. The gag reflex of some patients may be so severe that patients (and operating clinician) may favour extraction of any painful, infected teeth as opposed to more lengthy and complicated procedures such as root canal therapy. However, consistently adopting this approach may render the gagging patient completely edentulous. Such patients may then present to the dental surgeon requesting tooth replacement with some form of dentur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…9 This problem was solved in the patient by desensitizing her to external stimuli employing acrylic training plates and using a modified Krols technique while registering the impression. 10,11 Cu-sil dentures were designed to preserve the remaining natural teeth and have a good influence on denture retention and stability. 12 The patient's proclined anterior maxillary ridge and anterior undercut was leveraged for our advantage, using flangeless denture and resilient liners.…”
Section: Discussionmentioning
confidence: 99%
“…9 This problem was solved in the patient by desensitizing her to external stimuli employing acrylic training plates and using a modified Krols technique while registering the impression. 10,11 Cu-sil dentures were designed to preserve the remaining natural teeth and have a good influence on denture retention and stability. 12 The patient's proclined anterior maxillary ridge and anterior undercut was leveraged for our advantage, using flangeless denture and resilient liners.…”
Section: Discussionmentioning
confidence: 99%
“…31 This approach highlights the need for individualized management of patients with severe gag reflexes, with a focus on customized interventions to improve prosthesis acceptance and patient well-being. 26…”
Section: Treatment Methods For Removable Denture Patientsmentioning
confidence: 99%
“…The posterior extension is quite subjective, and it mainly depends on the intensity of the gag that the patient presents with. [13][14][15] In an article by Ali et al, it has been recommended to scribe multiple post dam areas in the master cast or a duplicate of the cast. Furthermore, they found that the denture bases were retentive in the oral cavity without the use of adhesives in spite of the extension being short.…”
Section: Training Denture Basesmentioning
confidence: 99%
“…The extension of the training denture base must be to the full functional sulcus depth and extend as much as possible posteriorly. The posterior extension is quite subjective, and it mainly depends on the intensity of the gag that the patient presents with 13–15 . In an article by Ali et al, it has been recommended to scribe multiple post dam areas in the master cast or a duplicate of the cast.…”
Section: Management Of Gag Reflexmentioning
confidence: 99%